AN ANALYSIS OF THE CHALLENGES FACED BY THE SCHOOL MANAGER WITH REGARD TO THE INCLUSIVE EDUCATION OF DEAF STUDENTS - Arouca, Nelcilandia Figueiredo da Silva; Silva, Ana Paula Teixeira da; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
The inclusion of deaf people is gradually being commonin collective environments, especially in the educational sphere. This is because since the beginning people with some disability did not even have the opportunity to live, a reality that is being changed in recent years. For this purpose, this article has as its main objective the analysis of dilemmas presented to managers in the school direction and, essentially, offered to all students. To this end, this work was developed on the reading and understanding of official regulatory documents, as well as based on theorists such as Libâneo (2004), Luck (2008), Lacerda (2002), Mantoan (1998), Ricardo (2018) and among other specialists in the area of management and pedagogical coordination. Methodologically, this research was based on bibliographic research, which, in turn, not only highlights the problems that exist in this school space, but also seeks to present how institutionally deaf students should be attended by regular schools. Emphasizing the importance of using the Brazilian Sign Language (LIBRAS) in this inclusion process, which, in short, enables an egalitarian and efficient education, since deaf students have the right to live together and be formed in an environment of socialization and interaction, aspects offered together with the school space.